2012
DOI: 10.1038/cgt.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to the INSM1 promoter to preserve specificity and activity for use in adenoviral gene therapy of neuroendocrine carcinomas

Abstract: The INSM1 gene encodes a transcriptional repressor that is exclusively expressed in neuronal and neuroendocrine tissue during embryonic development that is re-activated in neuroendocrine tumors. Using the 1.7 kbp INSM1 promoter, an adenoviral HSV thymidine kinase gene therapy was tested for the treatment of neuroendocrine tumors. An unforeseen interference on the INSM1 promoter specificity from the adenoviral genome was observed. Attempts were made to protect the INSM1 promoter from the influence of essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…To generate an adenoviral vector that is useful for the diagnosis of INSM1-positive NE tumors, we constructed the first generation modified INSM1-promoter by inserting a full HS4 insulator sequence upstream of the INSM1-promoter (~1.7 kb) along with two NRSE enhancer sequences in tandem repeats downstream and Luc2 gene ( Fig. 1A) (22). The modified INSM1-promoter drives a downstream Metridia luciferase gene, resulting in the construct Ad-HS4ins-INSM1p-2xNRSE-Metridia (Ad-INSM1p-Met) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To generate an adenoviral vector that is useful for the diagnosis of INSM1-positive NE tumors, we constructed the first generation modified INSM1-promoter by inserting a full HS4 insulator sequence upstream of the INSM1-promoter (~1.7 kb) along with two NRSE enhancer sequences in tandem repeats downstream and Luc2 gene ( Fig. 1A) (22). The modified INSM1-promoter drives a downstream Metridia luciferase gene, resulting in the construct Ad-HS4ins-INSM1p-2xNRSE-Metridia (Ad-INSM1p-Met) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the original INSM1-promoter possesses NE-tumor specificity, it was discovered that the promoter loses its specificity when used in an adenoviral setting. In a recent study, Akerstrom et al demonstrated that an INSM1-promoter driven adenoviral reporter construct displayed non-specific expression after tail vein injection in an in vivo mouse model (22). It was hypothesized that this loss of specificity was due to the presence of overpowering viral enhancers that were otherwise not present in normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations